Evaluasi Sistem Rekam Medis Elektronik Menggunakan Model HOT-Fit di RS Pelabuhan Palembang - Suci Rizki Amelia; Aditya Bayu Pratama; Airin Bismarulla Putri; Ananda Iqbal Fanany; Ardio Rizky Tansil Tan (CV. ITTC INDONESIA, 2026)
The implementation of electronic medical records (RME) in hospitals is a mandate of the Minister of Health Regulation Number 24 of 2022 to realize the digital transformation of National Health. However, the transition from paper-based to digital systems often faces complex challenges involving human aspects, organizational governance, and technological infrastructure readiness. This study aims to evaluate the influence of human components (Human), Organization (Organization), and Technology (Technology) to the Net Benefits (Net Benefits) of the application of RME at IHC Palembang Port Hospital. This study uses quantitative analytical methods with causal-correlational approach using cross-sectional design. The population of this study were all health workers and administrative staff active users of Electronic Medical Record system (RME) in Pelabuhan Palesebanyak 239 respondents using purposive sampling technique. Data collection was conducted through the deployment of a four-point Likert scale structured questionnaire and analyzed using multiple Linear regression analysis based on SPSS software.Partial test results showed that the human aspect (Human) has a positive and significant effect on Net Benefits (p = 0.007), and aspects of Technology (Technology) proved to have the most powerful and dominant positive influence on Net Benefits (p = 0.000). Simultaneously, the three components of HOT-Fit significantly affect the Net Benefits F count = 18.432; p = 0.000 with a coefficient of determination of 52.3%..In conclusion, digital transformation at Palembang Port hospital is already on the right track through system reliability and medical staff readiness. However, management is advised to intervene in organizational weaknesses through the provision of regular refresher training and strengthening the 24-hour IT helpdesk team in order to realize the quality of complete health services.